Invigorating ocean boundary current systems around Australia during 1979–2014: As simulated in a near‐global eddy‐resolving ocean model. Issue 5 (22nd May 2016) - Feng, Ming; Zhang, Xuebin; Oke, Peter; Monselesan, Didier; Chamberlain, Matthew; Matear, Richard; Schiller, Andreas
Abstract: Ocean boundary currents, transporting water masses and marine biota along the coastlines, are important for regional climate and marine ecosystem functions. In this study, we review the dominant multi‐decadal trends of ocean boundary currents around Australia. Using an eddy‐resolving global ocean circulation model, this study has revealed that the major ocean boundary current systems around Australia, the East Australian Current (EAC), the Indonesian Throughflow (ITF), the Leeuwin Current, the South Australian Current and the Flinders Current, have strengthened during 1979–2014, consistent with existing observations. Eddy energetics in the EAC, the ITF/South Equatorial Current in the southeast Indian Ocean, and the Leeuwin Current have also enhanced during the same period. The multi‐decadal strengthening of the ocean boundary current systems are primarily driven by large scale wind patterns associated with the dominant modes of climate variability and change – the phase shift of the Inter‐decadal Pacific Oscillation/Pacific Decadal Oscillation strengthens the ITF and the Leeuwin Current/South Australian Current; and the poleward shift and strengthening of surface winds in the subtropical gyres reinforce the EAC and the Flinders Current. The invigorating ocean boundary current systems have induced extreme oceanographic conditions along the Australian coastlines in recent years, including the poleward shift of marine ecosystems off the east coast of Australia and the consecutive Ningaloo Niño – marine heatwave events off the west coast during 2011–2013. Understanding long‐term trends and decadal variations of the ocean boundary currents is crucial to project future changes of the coastal marine systems under the influence of human‐induced greenhouse gas forcing. Key Points: Decadal trends of ocean boundary current systems simulated in a hydrodynamic model Enhanced current transport and eddy kinetic energy around Australia Variations of the dominant climate modes are important for boundary current variability